(untitled) - S PURI, YUNDA (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
This research aims to test the correlation between Adversity Intelligence and interest in entrepreneurship Data collecting conducted by disseminating questionnaire. Responder in research represent the student of the 3rd grade marketing student of SMKN 1 Surabaya. The correlation between Adversity Intelligence and interest in entrepreneurship analysed to use the Pearson Product Moment correlation. Result indicate that there are positive and significant correlation between Adversity Intelligence and entrepreneurship intention. Analysis result have known that R2 is 55,6% that influenced percentage of Adversity Intelligence to interest in entrepreneurship is 55,6% and other factor is 44,4% is determined by other variables outside of the study. Keywords: adversity quotien, interest in entrepreneurship